Association Between Cleft Lip and/or Cleft Palate and Family History of Cancer: A Case-Control Study. (April 2018) - Bui, Anthony H.; Ayub, Ayisha; Ahmed, Mairaj K.; Taioli, Emanuela; Taub, Peter J.
Abstract : Background: Cleft lip and/or cleft palate (CL ± P) are among the most common congenital anomalies. Nevertheless, their etiologies remain poorly understood. Several studies have demonstrated increased rates of cancer among patients with CL ± P and their relatives, as well as increased risk of CL ± P among family members of cancer survivors. In addition, a number of possible genetic associations between cancer and CL ± P have been identified. However, these studies are limited by confounding factors that may be prevalent in these patients, such as tobacco exposure and perinatal complications. The purpose of this study was to quantitatively evaluate the association between family history of cancer and development of CL ± P in the child. Methods: A case-control study was conducted at the Cleft Hospital and the Bashir Hospital in Gujrat, Pakistan from December 2015 to December 2016. All new cases of CL ± P at the Cleft Hospital were included. Sociodemographically similar patients without congenital malformations at the Bashir Hospital served as controls. Risk factors associated with CL ± P were identified through bivariate analyses. Multiple logistic regressions were performed to calculate adjusted odds ratios of developing CL ± P. Results: There were 137 patients with CL ± P and 147 controls in the study. The following factors were statistically significantly associated with development of cleft: history of cancer in the family ( P < 0.001), complications during pregnancy ( P = 0.02), maternal hypertension during pregnancy ( P = 0.01), mother not on any medications ( P < 0.001), consanguineous marriage (parents are first or second cousins) ( P = 0.03), lower socioeconomic status ( P < 0.001), having a parent who smokes ( P = 0.001), and history of miscarriage ( P = 0.01). After adjustment for these variables, having a history of cancer in the family was independently associated with a 5.19 times increased odds of the child being born with CL ± P (95% confidence interval [CI], 1.57–17.03). Middle-class socioeconomic status (compared with lower) (odds ratio [OR], 0.36; 95% CI, 0.16–0.83), having a smoking parent (OR, 2.12; 95% CI, 1.05–4.28), and history of miscarriage (OR, 4.60; 95% CI, 1.21–17.54) were also statistically significantly associated with CL ± P within this model. Conclusions: This study provides evidence for a relationship between CL ± P and cancer that has been adjusted for confounders traditionally associated with patients with CL ± P, thereby supporting the evidence of shared environmental and/or genetic etiologies.